Fate and Persistence of Crude Oil Stranded on a Sheltered Beach - Owens, Edwards H.; Harper, John R.; Robson, Wishart; Boehm, Paul D. (ARCTIC, 1987)
Detailed observations, mapping and sampling were conducted following an experimental spill of 15 cu m of crude oil adjacent to the coast at Cape Hatt, Baffin Island, N.W.T. The beach could not retain all of the oil that reached the shoreline, and as a result, one-third of the spill oil was recovered in cleanup activities on the water, approximately one-third was lost to the atmosphere and to the ocean and one-third remained stranded on the intertidal zone. The stranded oil was subject to natural cleaning processes during approximately 6 months of open-water periods from 1981 to 1983. Over this period the surface area of oil cover was reduced by approximately half, whereas estimates indicate that 80% of the oil initially stranded (5.3 cu m) was removed. This natural removal of stranded oil occurred in a very sheltered environment. The reduction of the surface area and of the volume of oil resulted primarily from the physical processes associated with wave activity and ground-water leaching. By 1983 an asphalt pavement had developed in the upper intertidal zone on the beach-face slope. Total hydrocarbon concentrations of samples collected from the asphalt pavement indicated a significant increase in oil-in-sediment values in this zone to concentrations in the order of 2-5%. Oil removed from the beach was transported into the adjacent nearshore bottom sediments, where oil concentrations increased sixfold between 1981 and 1983. Physio-chemical weathering rates were relatively rapid immediately following the release of the oil, as the lower molecular weight (C1 to C10) hydrocarbons evaporated. Subsequent physio-chemical changes were heterogeneous . The primary conclusion from the investigations undertaken to date is that oil is removed in substantial quantities from the intertidal zone even in such a sheltered, low-energy arctic environment. Similar changes should also be expected from comparable environments in lower latitudes.Key words: oil spill, natural oil weathering, asphalt pavement, beached oil Mots clés: ...